Correlation of esophageal pressure‐flow analysis findings with bolus transit patterns on videofluoroscopy. Issue 2 (17th December 2014) - Omari, T. I.; Szczesniak, M. M.; Maclean, J.; Myers, J. C.; Rommel, N.; Cock, C.; Cook, I. J.
Summary: Pressure‐flow analysis quantifies the interactions between bolus transport and pressure generation. We undertook a pilot study to assess the interrelationships between pressure‐flow metrics and fluoroscopically determined bolus clearance and bolus transport across the esophagogastric junction (EGJ). We hypothesized that findings of abnormal pressure‐flow metrics would correlate with impaired bolus clearance and reduced flow across the EGJ. Videofluoroscopic images, impedance, and pressure were recorded simultaneously in nine patients with dysphagia (62–82 years, seven male) tested with liquid barium boluses. A 3.6 mm diameter solid‐state catheter with 25 × 1 cm pressure/12 × 2 cm impedance was utilized. Swallowed bolus clearance was assessed using a validated 7‐point radiological bolus transport scale. The cumulative period of bolus flow across the EGJ was also fluoroscopically measured (EGJ flow time). Pressure only parameters included the length of breaks in the 20 mmHg iso‐contour and the 4 second integrated EGJ relaxation pressure (IRP4s). Pressure‐flow metrics were calculated for the distal esophagus, these were: time from nadir impedance to peak pressure (TNadImp to PeakP) to quantify bolus flow timing; pressure flow index (PFI) to integrate bolus pressurization and flow timing; and impedance ratio (IR) to assess bolus clearance. When compared with controls, patients had longer peristaltic breaks, higher IRs, and higher residual EGJ relaxation pressures (break length of 8 [2, 13] vs. 2 [0, 2] cm, P = 0.027; IR 0.5 ± 0.1 vs. 0.3 ± 0.0, P = 0.019; IRP4s 11 ± 2 vs. 6 ± 1 mmHg, P = 0.070). There was a significant positive correlation between higher bolus transport scores and longer peristaltic breaks (Spearman correlation r = 0.895, P < 0.001) and with higher IRs (r = 0.661, P < 0.05). Diminished EGJ flow times correlated with a shorter TNadImp to PeakP (r = −0.733, P < 0.05) and a higher IR (r = −0.750, P < 0.05). Longer peristaltic breaks and higher IR correlate with failed bolus clearance on videofluoroscopy. The metric TNadImp to PeakP appears to be a marker of the period of time over which the bolus flows across the EGJ.